P‐Type Polar Transition of Chemically Doped Multilayer MoS2 Transistor. Issue 12 (25th January 2016) - Liu, Xiaochi; Qu, Deshun; Ryu, Jungjin; Ahmed, Faisal; Yang, Zheng; Lee, Daeyeong; Yoo, Won Jong
Abstract : A high‐performance multilayer MoS2 p‐type field‐effect transistor is realized via controllable chemical doping, which shows an excellent on/off ratio of 10 9 and a maximum hole mobility of 132 cm 2 V −1 s −1 at 133 K. The developed technique will enable 2D materials to be used for future high‐efficiency and low‐power semiconductor device applications.